Transfection of cells from patients with leukocyte adhesion deficiency with an integrin beta subunit (CD18) restores lymphocyte function-associated antigen-1 expression and function. - Hibbs, M L (1990)
Leukocyte adhesion deficiency (LAD) is an inherited immunodeficiency disease that is characterized by the deficient expression of the leukocyte adhesion glycoproteins lymphocyte function-associated antigen-1 (LFA-1), Mac-1, and p150,95. This loss of expression is attributed to heterogeneous defects in the common beta subunit shared by these glycoproteins. Here we demonstrate that expression of the LFA-1 alpha beta heterodimer in EBV-transformed B lymphoblastoid cells from LAD patients can be recovered after transfection with the beta subunit cDNA contained in an EBV-based vector. Four patients with differing severities of LAD comprising three distinct classes of mutations were studied. Flow cytometry analysis of stably transfected patient cells revealed near normal levels of expression of both the alpha and beta chains of LFA-1, and immunoprecipitation studies confirmed that fully processed alpha and beta chains were being expressed at the cell surface. In addition, Northern analysis of mRNA expression also demonstrated that the transfected LAD patient cells were expressing high quantities of exogenous beta subunit mRNA. Functional studies such as homotypic adhesion and adhesion to a purified counterreceptor for LFA-1, intracellular adhesion molecule-1, demonstrated that LFA-1 function had been restored in the stably transfected LAD patient cell lines. These studies unequivocally show that the defect in cells from patients with LAD is in the leukocyte integrin beta subunit.